Risk of biodiversity extinction in Gunung Merapi National Park : Spatial assession - Hero Marhaento; Lies Rahayu Wijayanti Faida (Jurnal Ilmu Kehutanan)
The Mount Merapi (MM) has a unique landscape and becomes the habitat for mountainous species in the central Java, Indonesia. However, high volcanic activities and massive public pressure on its natural resources have increased the risk of biodiversity extinction in the MM. This study aims to assess the spatial risk of biodiversity extinction in the Mount Merapi National Park (MMNP). The risk analysis has been done by spatially measuring the risk elements i.e. hazard area, element at risk, and vulnerability rate. A Focus Group Discussion has been done to define and to identify components of each risk element. A spatial analysis using ArcGIS 10.1 has been used to measure the risk. The results showed that MMNP have three levels of risks: high risk level area (2185.6 ha, 35. 6%), moderate risk area (3910.1 ha, 63.6%) and low risk area (49.8 ha, 0.8%). The high risk areas were located in Resort Pengelolaan Taman Nasional (RPTN) Dukun in Magelang Distict, RPTN Turi-Pakem in Sleman District, and RPTN Kemalang in Klaten District.